KONSTRUK DARI BRAND POSITIONING UNTUK MENGUKUR PERSEPSI KONSUMEN TERHADAP BRAND PT X - Rakhdiny Sustaningrum (Universitas Musamus,Merauke,Papua, 2017)
This study aims to factors that affect brand awareness and brand positioning on PT X products. The research method used survey with data collection through questionnaire. Quantitative data analysis using SEM-PLS. The results showed that brand identity, brand personality, brand communication each partially significant effect on brand awareness. Then, brand awareness has a significant effect on brand image, and brang image significant effect on brand positioning. In conclusion, consumers give a positive perception on brand PT X so that consumers are interested to use it.